Exploring Students’ Critical Thinking Skills with A Problem-based Learning Model Assisted by Animated Video in Static Fluid Learning - Lambang Subagiyo; Sonia Ayu Riani; Abdul Hakim (Berkala Ilmiah Pendidikan Fisika, 2023)
This study was motivated by the necessity of improving students' critical thinking skills in the era of Industry 4.0. We developed and implemented a problem-based learning model (PBL) assisted by animated video as a learning tool made by using Adobe After Effects to improve the critical thinking skills of high school students using Problem-Based Learning as the instructional model in static fluid learning. This study applied a quasi-experimental one-group pretest-posttest design with a quantitative approach and purposive sampling. This study's samples included students of Class XI MIPA 3 of one of the high schools in Samarinda. This study's instrument consisted of essay questions about static fluids in physics that contained six indicators of critical thinking abilities: (a) identifying problems, (b) giving arguments, (c) deductive reasoning, (d) inductive reasoning, (e) evaluating, and (f) problem-solving and decision making. The results show that it is feasible and effective to adapt animated videos as learning media for educational content to improve students' critical thinking skills. The most improved aspect was on the deductive reasoning with an average N-Gain score of 0.93 by a 78-point difference between the pretest and posttests, and the least improved aspect was on the inductive reasoning aspect with an average N-Gain score of 0.63 by the 38-point difference between the pretest and posttests and an Effect Size of 3.43 in the very large category. We conclude that improving students’ critical thinking skills using a problem-based learning model assisted by animated video in static fluid learning is effective.